2013
DOI: 10.4100/jhse.2012.82.06
|View full text |Cite
|
Sign up to set email alerts
|

Time-motion analysis in women’s team handball: importance of aerobic performance

Abstract: Manchado C, Pers J, Navarro F, Han A, Sung E, Platen P. Time-motion analysis in women's team handball: importance of aerobic performance. J. Hum. Sport Exerc. Vol. 8, No. 2, pp. 376-390, 2013. Women's handball is a sport, which has seen an accelerated development over the last decade. Data on movement patterns in combination with physiological demands are nearly nonexistent in the literature. The aim of this study was twofold: first, to analyze the horizontal movement pattern, including the sprint accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 16 publications
(3 reference statements)
4
30
2
15
Order By: Relevance
“…They reported that backs and pivots had the highest number of CoD (37.9 ± 9.2 and 35.4 ± 11.1 CoD per match for backs and pivots, respectively), which is partly supported by this study. Despite the difficulties for a direct comparisons between the current study, and other studies that have investigated physical demands in team handball, there appears to be little doubt that HIE actions are an important element for physical performance in both male 6,25 and female 23,26 team handball. This underlines the need for specific training for repeated HIE in addition to a need for well-developed muscle strength.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…They reported that backs and pivots had the highest number of CoD (37.9 ± 9.2 and 35.4 ± 11.1 CoD per match for backs and pivots, respectively), which is partly supported by this study. Despite the difficulties for a direct comparisons between the current study, and other studies that have investigated physical demands in team handball, there appears to be little doubt that HIE actions are an important element for physical performance in both male 6,25 and female 23,26 team handball. This underlines the need for specific training for repeated HIE in addition to a need for well-developed muscle strength.…”
Section: Resultsmentioning
confidence: 73%
“…Heart rate measurements from team handball match play show some difference between playing positions 6,11,23 . Goalkeepers show lower values than all other positions 23 , which is in line with the lower Player Load™·min -1 shown in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Players require well-developed aerobic capacity to maintain maximal performance throughout the match and to recover faster during the short periods of lower intensity or rest [9,11,12]. The handball players with a higher VO 2max can run at higher speeds during a match and can sprint more [14]. [32].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic endurance is one of the main fitness components, important for success in soccer and handball [7,13,14]. VO 2max andanaerobic threshold (AT) are the most important parameters used in the evaluation of aerobic endurance [6,15,16].…”
Section: Introductionmentioning
confidence: 99%